An updated checklist of decapod crustaceans (infraorders Astacidea, Thalassinidea, Polychelida, Palinura, and Anomura) from the northern and northeastern Brazilian coast - Coelho, Petrônio Alves; de Almeida, Alexandre Oliveira; Bezerra, Luis Ernesto Arruda; de Souza-Filho, Jesser Fidelis (Zootaxa, 2007)
A checklist of the decapod crustacean species from the infraorders Astacidea, Thalassinidea, Polychelida, Palinura, and Anomura from the northern and northeastern (N/NE) Brazilian coast based on literature and material deposited in the carcinological collection of the Universidade Federal de Pernambuco, Recife, Brazil, is provided. The list includes marine and estuarine species reported at least once to each of the studied area, including the oceanic islands and banks along the N/NE Brazil. A total of 146 species is reported, corresponding to an increase of 32.7% when compared to the data published in Paulo Young’s Catalogue (1998). The most representative infraorder concerning number of species is Anomura, represented in N/NE Brazil by 90 species and 10 families, followed by Thalassinidea, with 36 species and 6 families, Palinura, with 14 species and 4 families and, finally, Astacidea, which comprises 6 species and 2 families. Families with highest species richness were Porcellanidae (20), Diogenidae (19), Paguridae (18) and Galatheidae (15), all of them included in the infraorder Anomura. Zoogeographic affinities regarding the species are briefly discussed